The politics of policy failure in Ghana: The case of oil palm - Asante, K.T. (World Development Perspectives, 2023)
The paper argues that political economy factors have hindered the development of the oil palm value chain in Ghana, which has consistently underperformed despite significant policy support and the sector’s strategic importance to the national economy. These factors include political instability between the mid-1960s and early 1980s, as well as the emergence of a competitive clientelist political settlement since the country’s return to constitutional rule. Drawing on key informant interviews and documentary sources, the paper demonstrates that policies over the past two decades have failed to address the peculiar nature of the value chain, which is bifurcated into a smallholder/artisanal sub-sector and an estate/industrial processing sub-sector. Since the 1990s, one aspect of policy failure in the sector has been the ‘paradox of good intentions’ that arises from the simultaneous pursuit of economic transformation and inclusive development in a political context described by some scholars as ’strong democracy, weak state’. The logic of electoral competition shortens politicians’ time horizons, predisposing them to prioritise highly visible distributive policies (like input subsidies) over structural reforms (like land tenure issues or solving market frictions). Consequently, despite almost two centuries of continuous policy support, the sector’s productivity remains at the same level it would have been if it had been left to operate without any state assistance.
Research Article
Keywords: Policy failure; Oil palm; Competitive clientelism